A Structural Model for the Iron–Nitrosyl Adduct of Gentisate Dioxygenase. Issue 44 (27th November 2018) - Banerjee, Atanu; Li, Jia; Speelman, Amy L.; White, Corey J.; Pawlak, Piotr L.; Brennessel, William W.; Lehnert, Nicolai; Chavez, Ferman A.
Abstract : We present the synthesis, properties, and characterization of [Fe(T1Et4iPrIP)(NO)(H2 O)2 ](OTf)2 (1 ) {T1Et4iPrIP = Tris(1‐ethyl‐4‐isopropyl‐imidazolyl)phosphine} as a model for the nitrosyl adduct of gentisate 1, 2‐dioxygenase (GDO). The further characterization of [Fe(T1Et4iPrIP)(THF)(NO)(OTf)](OTf) (2 ) which was previously communicated (Inorg. Chem.2014, 53, 5414) is also presented. The weighted average Fe–N–O angle of 162° for1 is very close to linear (≥ 165°) for these types of complexes. The coordinated water ligands participate in hydrogen bonding interactions. The spectral properties (EPR, UV/Vis, FTIR) for1 are compared with2 and found to be quite comparable. Complex1 closely follows the relationship between the Fe–N–O angle and NO vibrational frequency which was previously identified for six‐coordinate FeNO 7 complexes. Liquid FTIR studies on2 indicate that the ν(NO) vibration position is sensitive to solvent shifting to lower energy (relative to the solid) in donor solvent THF and shifting to higher energy in dichloromethane. The basis for this behavior is discussed. The K eq for NO binding in2 was calculated in THF and found to be 470m –1 . Density functional theory (DFT) studies on1 indicate donation of electron density to the iron center from the π* orbitals of formally NO – . Such a donation accounts for the near linearity of the Fe–N–O bond and the large ν(NO) value of 1791 cm –1 . Abstract : We report a model for the iron–nitrosyl adduct of gentisate dioxygenase {[Fe(T1Et4iPrIP)(NO)(H2 O)2 ](OTf)2, 1 }. Complex1 is synthesized by the addition of 2 equiv. water to [Fe(T1Et4iPrIP)(THF)(NO)(OTf)](OTf) (2 ). A correlation between the solid‐state Fe–N–O angle and ν(NO) is elaborated and the K eq in THF for the reversible binding of NO to2 is reported. The influence of solvent on the value of ν(NO) for2 is also discussed.